2014
DOI: 10.1007/s11064-014-1499-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Permeability and Brain Uptake Mechanism of Kainic Acid and Dihydrokainic Acid

Abstract: The glutamatergic neurotransmitter system is involved in important neurophysiological processes and thus constitutes a promising target for the treatment of neurological diseases. The two ionotropic glutamate receptor agonists kainic acid (KA) and dihydrokainic acid (DHK) have been used as research tools in various in vivo central nervous system disease models in rodents, as well as being templates in the design of novel ligands affecting the glutamatergic system. Both molecules are highly polar but yet capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…LFP recordings and concomitant expression of Ca 2+ indicators in neurons confirmed a successful blockage of neurons. Since kainate to a very little degree passes the blood–brain barrier ( Gynther et al 2015 ), only a small fraction of kainate reaches the brain interstitium following intraperitoneal administration. Typical doses that are sufficient to elicit epileptiform activity in slices are as low as, or even lower than, 500 nM ( Ben-Ari and Cossart 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…LFP recordings and concomitant expression of Ca 2+ indicators in neurons confirmed a successful blockage of neurons. Since kainate to a very little degree passes the blood–brain barrier ( Gynther et al 2015 ), only a small fraction of kainate reaches the brain interstitium following intraperitoneal administration. Typical doses that are sufficient to elicit epileptiform activity in slices are as low as, or even lower than, 500 nM ( Ben-Ari and Cossart 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ionotropic glutamate agonists selectively bind to different types of glutamate receptors and transmit their stimulation to neurons and provide neuronal activation [ 26 ]. It has been reported that glutamate agonists, including kainic acid [ 27 , 28 , 29 ], AMPA [ 30 , 31 ], and NMDA [ 31 , 32 , 33 , 34 ], can reach the central nervous system by passing the blood-brain barrier. The present study showed that these agonists can reach the nesfatin-1 neurons in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature have suggested that kainic acid [25][26][27][28], AMPA [29,30], and NMDA [29][30][31][32][33] can cross the blood-brain barrier and reach the central nervous system. Our immunohistochemical studies showed that systemic administration of ionotropic non-NMDA and NMDA glutamate receptor agonists directly or indirectly activate neuronostatin neurons at different rates and that the intracellular pathway of c-Fos protein plays a role in this activation.…”
Section: Investigation Of the Glutamatergic System Effects And Activamentioning
confidence: 99%